Lipoxygenase Enzymes, Oligosaccharides (Raffinose and Stachyose) and 11sA4 and A5 Globulins of Glycinin Present in Soybean Meal Are Not Drivers of Enteritis in Juvenile Atlantic Salmon (Salmo salar) - Artur N. Rombenso; David Blyth; Andrew T. James; Teisha Nikolaou; Cedric J. Simon (Applied Sciences, 2021)
Soybean meal has been largely investigated and commercially used in fish nutrition. However, its inclusion levels have been carefully considered due to the presence of antinutritional factors, which depending on a series of factors might induce gut inflammation damaging the mucosal integrity and causing enteritis. Several strategies including genetic engineering have been applied attempting to reduce or eliminate some of the antinutritional factors. Accordingly, we assessed the intestinal health of juvenile Atlantic salmon fed high levels of speciality soybean genotypes with reduced-to-no content amounts of lipoxygenases, altered glycinin profile and reduced levels of oligosaccharides. No major signs of enteritis, only indication of enteritis progression, was noticed in the soybean meal-based diets illustrated by mild changes in distal intestine morphology. Whereas fish, fed fishmeal control feeds, displayed normal distal intestine integrity. Speciality soybean types did not improve intestinal health of juvenile Atlantic salmon suggesting these antinutrients are not drivers of the intestinal inflammatory process in this species. No additional benefits in terms of production performance or blood biochemistry were noticed in the speciality soybean types compared to the traditional soybean.